Nociones básicas para la iniciación a las matemáticas en los niños y niñas de primer año de educación básica paralelo “B” de la Escuela Fiscal Isidro Ayora en la ciudad de Latacunga, provincia de Cotopaxi, durante el periodo académico 2014-2015 - Chancusi Ronda, Lisenia Marisol (2015)
This research was to strengthen the children importance of the basic notions as a tool in the mathematics initiation of first year of basic education “Isidro Ayora” school, same that is the fundamental base for the students of this instution with who will have relation with necessary mathematic knowledge, by using logic mathematic thinking manual development being this one a innate capacity to allow them to explore and discover the environment that surrounded through the games development. This research was an input for children students´ parents, teachers of first year of basic education and headmaster institution. The interview, survey and observation field were techniques used to collect information that helped us to get the necessary data. The statistical analyze percentage was used to analyze the relevant information in order to get results. Mathematics favor to the good mental structure development providing a tool to know and perceive the environment. The majority of teachers didn´t have the appropriate methodology for teaching this themes whereby the knowledge they are not transmitted toward their students.